Microbusiness: A new social business model to alleviate poverty in developing countries? - Heervä, Jenni (My University, 2013)
Poverty alleviation views have shifted from seeing the poor as victims or as potential consumers, to seeing them as gainers. Social businesses include microfinancing and microfranchising, which engage people at the bottom of the pyramid using business instead of charity. There are, however, social business firms that do not fit to the existing social business model theory. These firms provide markets to poor producers and mix traditional, local craftsmanship with western design. Social business models evolve faster than the academic literature can study them. This study contributes to filling this gap. The purpose of this Master’s thesis is to develop the concept of social business as poverty alleviation method in developing countries. It also aims; 1) to describe the means for poverty alleviation in developing countries; 2) to introduce microbusiness as a social business model; and 3) to examine the challenges of microbusinesses. Qualitative case study is used as a research strategy and theme interviews as a data collecting method. The empirical data is gathered from four interviews of Finnish or Finnish-owned firms that employ microbusiness – Mifuko, Tensira, Mangomaa and Tikau – and this is supported with secondary data including articles on case companies. The results show that microbusiness is a valid new social business model that aims at poverty alleviation by engaging the poor at the bottom of the pyramid. It is possible to map the value proposition, value constellation, and economic and social profit equations of the case firms. Two major types of firms emerge from the results; the first consists of design-oriented firms that emphasize the quality and design of the products, and the second consists of bazaar-like firms whose product portfolio is less sophisticated and who promote more the stories of the products – not the design. All microbusiness firms provide markets, promote traditional handicrafts, form close relationships to their producers, and aim at enhancing lives through their businesses. The attitudes towards social businesses are sometimes negative, but this is changing for the better. In conclusion, microbusiness answers to two different needs at the same time – consumers’ needs for ethical products and the social needs of the producers – but the social need is the ultimate reason why the entrepreneurs started business. Microbusiness continues as a poverty alleviation tool that sees the poor as gainers; by providing them steady employment, microbusiness increases the poor’s self-esteem and enables them for a better living. Academic literature has not been able to offer enough alternative business models to cover all social businesses; the current study contributes to this by concluding that microbusiness is another social business model.